The Relationship Of Revitalization To The Sustainability Of The Cihapit Traditional Market: Pre-Production Of Documentary Film - Shelvira Alyya Putri Anjani; Nala Nandana Undiana (Cinematology: Journal Anthology of Film and Television Studies, 2021)
Revitalization is one of the government's efforts so that traditional markets can compete and survive amid the development of modern markets. This has been carried out in one of the markets in Bandung, namely Cihapit Market. This research was made with a quantitative method with a survey research design. The data used are the results of the use of survey research designs, the results of interviews through questionnaires of respondents from Cihapit Market traders regarding the effect of Revitalization that has been felt to date, which were tested by the Chi-Square method to see the relationship between Revitalization and the sustainability of traditional markets. The results of this study will test the hypothesis that has been made by the researcher, and show that revitalization is not related to the sustainability of the Cihapit Market to date. And also the results of this research will support the outcome of the documentary film projectKeywords: Revitalization, Market, Relationship.Documentary Film